2020
DOI: 10.1029/2019jg005266
|View full text |Cite
|
Sign up to set email alerts
|

CMIP5 Models Predict Rapid and Deep Soil Warming Over the 21st Century

Abstract: Despite the fundamental importance of soil temperature for Earth's carbon and energy budgets, ecosystem functioning, and agricultural production, studies of climate change impacts on soil processes have mainly relied on air temperatures, assuming they are accurate proxies for soil temperatures. We evaluated changes in soil temperature, moisture, and air temperature predicted over the 21st century from 14 Earth system models. The model ensemble predicted a global mean soil warming of 2.3 ± 0.7 and 4.5 ± 1.1 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 68 publications
4
36
0
Order By: Relevance
“…However, the net benefits of mitigation at higher atmospheric CO 2 become smaller if relative humidity decreases (a trend being already observed in Spain in Moratiel et al, 2010). Additionally, there is a general trend towards warmer and dryer soils that can further reduce water availability and increase drought stress for biocrusts (Soong et al, 2020). Field studies on this subject are still very rare, but a study conducted in the Mojave desert suggests that higher atmospheric CO 2 cannot mitigate the negative effects of drought on biocrust cover (Wertin et al, 2012).…”
Section: Relative Humidity Drives Climate Change Responses Of D Dimentioning
confidence: 94%
“…However, the net benefits of mitigation at higher atmospheric CO 2 become smaller if relative humidity decreases (a trend being already observed in Spain in Moratiel et al, 2010). Additionally, there is a general trend towards warmer and dryer soils that can further reduce water availability and increase drought stress for biocrusts (Soong et al, 2020). Field studies on this subject are still very rare, but a study conducted in the Mojave desert suggests that higher atmospheric CO 2 cannot mitigate the negative effects of drought on biocrust cover (Wertin et al, 2012).…”
Section: Relative Humidity Drives Climate Change Responses Of D Dimentioning
confidence: 94%
“…Each sample was analyzed twice, and the average results for each sample were recorded. Analytical precision was 0.2‰ for 13 C.…”
Section: Whole-ecosystem Warming and Elevated Atmospheric [Co 2 ]mentioning
confidence: 99%
“…1a). Capturing comprehensive peatland responses to climate change requires the use of active surface and deep-soil warming because deep-soil temperatures will naturally increase in concert with rising annual air temperatures [13][14][15] . Based on current greenhouse gas emission rates 16 , forcing estimates in line or greater than the RCP 8.5 scenario are likely to occur.…”
mentioning
confidence: 99%
“…Nevertheless, Soong et al (2020) showed the models do agree on the speed with which the warming signal is propagated through the most biologically active soil layers. Answering the question of whether shallow soils (1–5 cm depth) will warm faster than deep soils (100 cm depth), they showed no difference in warming rate predicted by the models.…”
Section: How Much Will Soil Warm?mentioning
confidence: 99%